The Correlation Between Social Environment Factor and Nurses’ Standard Vigilance Implementation in the Inpatient Room at Siti Rahmah Islamicic Hospital Padang in 2015 - Nita, Y; ., Almahdy; ., Harmawati (KnE Life Sciences, 2019)
Standard vigilance is an infection control universally either for the patient or the medical staffs. The number of occurance for needle punctured wound in inpatient room at Islamic Hospital Siti Rahmah in the amount of 2 until 3 times in a year, the usage of self protection equipment that is still less optimal, and the implementation of hand washed that is still not effective yet. The factor of social environment covering; organization, leadership, norms and group climate, communication, and operational procedures. The purpose of this research is to identify the correlation between social environment and the implementation of standard vigilance of the nurses in Inpatient Room at Islamic Hospital Siti Rahmah Padang. The research designed used was analytical cross-sectional on 46 nurses in inpatient room at Islamic Hospital Siti Rahmah Padang. The research results show that there is meaningful correlation between leadership and the implementation of standard vigilance (p = 0,007), while organization, norms and group climate, communication, operational procedure/SPO do not show meaningful correlation with the implementation of nurses’ standard vigilance. The results of this research can become information for the nurses that they need to add their knowledge through training related to the standard vigilance of nurses, especially in the case of hand washing, the usage of self-protection equipment, and managing the usage of needle and sharp objects. Keywords: social environment factor, nurse characteristic, the implementation of nurses’ standard vigilance